FACIES HETEROGENEITIES AND 3D POROSITY MODELLING IN AN OLIGOCENE (UPPER CHATTIAN) CARBONATE RAMP, SALENTO PENINSULA, SOUTHERN ITALY. (17th March 2020) - Brandano, M.; Tomassetti, L.; Trippetta, F.; Ruggieri, R.
Abstract : Appraisal of the volumes of fluid in a carbonate reservoir will typically require a reliable predictive model. This can be achieved by combining studies of well‐exposed carbonate successions with 3D models in order to obtain reliable quantitative data. In this paper, we present a detailed outcrop study and a 3D porosity model of a well‐exposed Oligocene carbonate ramp (Salento Peninsula, southern Italy) to investigate the nature of small‐scale facies and porosity heterogeneities. Porosity and permeability in the ramp carbonates appear to be controlled by the original mineralogy of skeletal components and by depositional textures. The aims of the study were therefore to identify the factors controlling porosity development in an undeformed carbonate ramp; to model the scale‐dependent heterogeneities characteristic of the facies associations; and finally to produce a 3D model of the porosity distribution. The upper Chattian Porto Badisco Calcarenite which crops out along the coast of the Salento Peninsula consists of six lithofacies ranging from inner ramp deposits to fine‐grained outer ramp calcarenites. The lithofacies are: inner ramp small benthic foraminiferal wackestone‐packstones associated with (i) sea grass meadows (SG) and (ii) coral mounds (CM) consisting of coral bioconstructions with a floatstone/packstone matrix; middle ramp (iii) large rotaliid packstones to wackestone‐packstones (LR), (iv) rhodolith floatstone‐rudstones (RF), and (v) large lepidocyclinid packstones (LL); and (vi) outer ramp fine‐grained bioclastic calcarenites (FC). A total of 38 samples collected from six stratigraphic sections (A, B, D, J, E, LO), measured in the Porto Badisco ravine, were investigated to discriminate the types of porosity. Effective and total porosity was measured using a helium pycnometer. The 3D porosity modelling was performed using PETREL™ 2016 software (Schlumberger). Four main types of porosity were recognized in the carbonates: interparticle, intraparticle, vuggy and mouldic. Primary porosity (inter‐ and intraparticle) is limited to middle ramp lithofacies (LL and LR) and outer ramp lithofacies (FC), whereas secondary porosity (vuggy and mouldic) was present in both inner ramp lithofacies (CM and SG) and middle ramp red algal lithofacies (RF). In the Porto Badisco carbonates, stratigraphic complexity and the distribution of primary porosity are controlled by lateral and vertical variations in depositional facies. Significant secondary porosity was produced by the dissolution of aragonitic and high‐magnesium calcite components, which are dominant in the sea‐grass and coral mound facies of the inner ramp and in the rhodolith floatstone‐rudstones of the middle ramp. 3D models were developed for both effective and total porosity distribution. The porosity models show a clear correlation with facies heterogeneities. However of the two models, the effective porosity model shows the best correlation with the 3D facies model, and shows a general increase in effective porosity basinwards in the middle ramp facies.